Peran Pendidikan Karater Dalam Pencegahan Bulliying di Ma Tanwirul Qulub - Fifin Ida Auliyah; M Dimas Faisal Afandi; M Ulil Albab; Muhammad Asrori; Deswita Auliyatul Maslukhah; Devi Puji Uswatun Khasanah; Indah Sari Nurul Abidah; Nurma Yulianti; Putri Ambar Kusuma (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Character education is an effort to shape students' personalities, This is a crucial aspect that needs to be applied by educators in the school environment. This is especially relevant in the midst of the rapid development of information technology that affects students' lives. This study aims to understand the role of education in bullying prevention efforts. This research was conducted using a qualitative method with a descriptive approach. The data collected was analyzed through the stages of data reduction, data presentation, and conclusion drawn. The respondents of this study were the Vice President of Student Affairs and students of MA Tanwirul Qulub Sungelebak Karanggeneng Lamongan. The results of this study reveal that teaching character education to students has an important role, because the instillation of these values can help prevent bullying behavior.